STEM education institutional change projects: examining enacted approaches through the lens of the Four Categories of Change Strategies Model - S. Feola; J. E. Lewis; J. D. McAlpin; L. B. Prevost; J. Skvoretz; M. Stains; B. A. Couch; B. Earl; J. P. Ziker; A. K. Lane; S. E. Shadle (SpringerOpen, 2023)
Abstract Background Enacting STEM education reform is a complex task and there are a variety of approaches that might be selected by change agents. When working on an institutional change project to impact multiple parts of the STEM education system, teams of change agents may select multiple strategies and tactics to enact at one time and over multiple years of a project. However, the literature lacks studies which document and analyze strategies and tactics used by change project teams in a way that can be useful for other change agents. The current study seeks to fill this gap by investigating National Science Foundation-funded change initiatives at three public research universities focused on encouraging the adoption of evidenced-based instructional practices by STEM faculty in order to understand the strategies used within and across projects. Results Qualitative framework analysis using the lens of the Henderson et al. (Journal of Research in Science Teaching 48(8): 952-984, 2011. https://doi.org/10.1002/tea.20439 ) Four Categories of Change Strategies Model showed that institutional projects enact a wide range of tactics that span the four strategies represented in the four categories of the model both across institutions and within each institution. The analysis documents a number of change tactics not previously described by the model and offers expanded definitions of the change processes that operate within each category in the context of institutional change projects. Conclusion This descriptive work advances our understanding of the breadth and depth of actions taken by institutional change initiatives and provides insights into types of variations that might be observed based on different institutional contexts. The current analysis both affirms the value of the original model and identifies expanded ways to think about the four categories within the context of institutional change projects.